2014
DOI: 10.1111/acer.12299
|View full text |Cite
|
Sign up to set email alerts
|

Event‐Related Potential Responses to the Acute and Chronic Effects of Alcohol in Adolescent and Adult Wistar Rats

Abstract: Background The present study explored the hypothesis that adolescent ethanol exposure may cause long lasting changes in ethanol sensitivity by exploring the age-related effects of acute alcohol on intoxication and on event-related potential (ERP) responses to acoustic stimuli in ethanol naïve adolescent and adult male Wistar rats and in adult rats that were exposed to chronic ethanol/control conditions during adolescence. Methods Ethanol naïve adolescent (postnatal day 32 (PD32)) and adult male rats (PD99) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 59 publications
4
19
0
Order By: Relevance
“…For instance, in rodents, the 2‐week period between postnatal days (P) 28–42 is the equivalent of the early to midadolescent period (∼12–18 years) in humans, while P43–55 is more comparable to the period of late adolescence/emerging adulthood in humans (∼18–25 years) (see Spear, ). To mimic binge drinking, alcohol was administered intraperitoneally, intragastrically (Vetreno & Crews, ), or using intermittent ethanol vapor exposure (e.g., Ehlers, Liu, Wills, & Crews, ; Ehlers, Desikan, & Wills, ) either intermittently or over several days to reach blood alcohol concentration (BAC) levels of 0.08 g/dl or higher (considered binge drinking levels, as defined by the National Institute on Alcohol Abuse and Alcoholism). For instance, one of the first adolescent models of binge drinking in rats (Pascual, Blanco, Cauli, Minarro, & Guerri, ) used an intraperitoneal injection of ethanol (3 g/kg) on 2 consecutive days at 48‐hr intervals over 14 days, and reached a BAC level of 0.16 g/dl.…”
Section: Animal Studies and Mechanisms Of Ethanol Action In The Adolementioning
confidence: 99%
“…For instance, in rodents, the 2‐week period between postnatal days (P) 28–42 is the equivalent of the early to midadolescent period (∼12–18 years) in humans, while P43–55 is more comparable to the period of late adolescence/emerging adulthood in humans (∼18–25 years) (see Spear, ). To mimic binge drinking, alcohol was administered intraperitoneally, intragastrically (Vetreno & Crews, ), or using intermittent ethanol vapor exposure (e.g., Ehlers, Liu, Wills, & Crews, ; Ehlers, Desikan, & Wills, ) either intermittently or over several days to reach blood alcohol concentration (BAC) levels of 0.08 g/dl or higher (considered binge drinking levels, as defined by the National Institute on Alcohol Abuse and Alcoholism). For instance, one of the first adolescent models of binge drinking in rats (Pascual, Blanco, Cauli, Minarro, & Guerri, ) used an intraperitoneal injection of ethanol (3 g/kg) on 2 consecutive days at 48‐hr intervals over 14 days, and reached a BAC level of 0.16 g/dl.…”
Section: Animal Studies and Mechanisms Of Ethanol Action In The Adolementioning
confidence: 99%
“…The same acute ethanol dose promoted 4–6 HZ power in the parietal cortex and hippocampus in adult Sprague-Dawley rats who had not received AIE exposure, whereas this ethanol effect was not evident in those exposed to AIE (Slawecki, 2002). Similarly, it is known that ethanol increases the latency of certain neocortical event-related potentials (ERPs), and does so less efficaciously in adolescent than adult rats (Ehlers et al, 2014). Interestingly, in the same study, when animals were exposed intermittently to ethanol vapor throughout adolescence and then tested in adulthood, their ERP latencies were less sensitive to acute ethanol than those of adult control animals.…”
Section: Retention Of Adolescent-typical Phenotypes After Aie: Elementioning
confidence: 99%
“…on; 10 hr. off) ethanol vapor exposure with Wistar rats (e.g., Ehlers et al, 2013; 2014). Timing of the exposure has also varied across studies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that chronic intermittent exposure to ethanol vapor during adolescence (14 hours exposure/10 hours no exposure, daily, over a 5-week period) can cause: increases in voluntary ethanol drinking, reductions in the size of the hippocampus as imaged by diffusion tensor imaging, reductions in measures of hippocampal neurogenesis, increases in the latency of the P300 component of the event-related potential, signs of behavioral disinhibition in the light/dark box and open field conflict test, immobility in the forced swim test, and reductions in cholinergic tone in the basal forebrain (see Criado and Ehlers, 2013; Ehlers et al, 2011, 2013a,b, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Adolescent rats display greater tolerance to the sedative effects of acute ethanol administration than adult rats, and regain consciousness at higher blood alcohol levels (Pian et al, 2008b; Silveri and Spear, 1998). For adult rats exposed to CIE during adolescence, the adolescent phenotype of reduced sensitivity to ethanol has been shown to be “retained” in behavioral measures (Slawecki, 2002; White et al, 2000 a,b), electrophysiological measures in the hippocampus (Fleming et al, 2012, 2013; Slawecki, 2002), and in the cortex (Ehlers et al, 2013c, 2014; Slawecki, 2002). Some authors have suggested that adolescent ethanol exposure may “lock-in” adolescent sensitivity to ethanol and then sustain it into adulthood (Fleming et al, 2012).…”
Section: Introductionmentioning
confidence: 99%